A263 FOCUSING ON THE FUTURE: REDUCING BARRIERS AND IMPROVING ACCESS TO IBD SPECIALTY CARE ACROSS CANADA. (15th March 2019) - Heisler, C; Kits, O; Veldhuyzen van Zanten, S; Jones, J
Abstract: Background: Canada has the highest age-adjusted incidence and prevalence rates of Inflammatory Bowel Disease (IBD) globally. Given its cumulative prevalence, the IBD clinical burden continues to grow. Limitations in accessing specialty healthcare services is not a new issue facing patients and healthcare providers. Despite this persistent problem, no research elucidating the patient perspective using qualitative approaches to compare and contrast the patient experience across Canada has been conducted. Aims: The aim of the current study was to elicit a qualitative stream of data to better understand phenomena related to access to healthcare for Canadians living with IBD from a patient-centered perspective. Methods: IBD patients (≥18 years of age) were recruited from gastroenterology clinics and communities through IBD specialists and Crohn's & Colitis Canada. Patients were recruited from both urban and rural locales to ensure adequate representation from geographically diverse regions. Focus groups provided a powerful and more naturalistic tool through which a focused understanding of the patient experience was derived. Co-facilitated by a researcher and a patient research partner, the focus groups were held in Nova Scotia, New Brunswick, Quebec, Ontario, Manitoba, Saskatchewan, Alberta, and British Columbia. Patient demographics were collected to contextualize observed themes. Themes were distilled through qualitative thematic analysis using Atlas.ti software to ascertain congruence or discordance of patient experiences. Eastern Canadian focus groups have been completed, with recruitment underway for the Western Canadian focus groups. Results: A total of 20 participants were recruited as of September 2018. The majority of participants were male (11/20, 55%) and were from urban/suburban regions (10/20, 50%). The mean age of participants was 44 years of age (SD=12 years, range=24 to 67 years). Preliminary analyses show that the main patient-identified barriers to accessing IBD care fall into the following categories: 1) Lack of multidisciplinary care (including psycho-social support), 2) Diagnostic delay, and 3) Inability to effectively receive and provide communication with healthcare providers. Solutions identified by patients included: 1) Integration of more holistic care into the clinical practice, 2) Readily accessible psychiatric and nutritional support, 3) Increased patient advocacy, and 4) Continuity and liaison through provision of a healthcare navigator resource. Conclusions: Healthcare access for IBD patients is complex. It is important to not only have a robust understanding of the healthcare system structure and processes but also the significant impact these factors have on patients. Access improvement research can be best tackled through patient-centered exploration of themes related to access to care. Funding Agencies: CIHR